Intraoperative Primary Tumor Identification and Margin Assessment in Head and Neck Unknown Primary Tumors. (March 2020) - Herruer, Jasmijn M.; Taylor, S. Mark; MacKay, Colin A.; Ubayasiri, Kishan M.; Lammers, Deanna; Kuta, Victoria; Bullock, Martin J.; Corsten, Martin J.; Trites, Jonathan R. B.; Rigby, Matthew H.
Objective: Surgical management of the unknown primary head and neck squamous cell carcinoma (UP HNSCC) remains controversial due to challenging clinical diagnosis. This study compares positron emission tomography–computed tomography (PET-CT) findings with intraoperative identification of primary tumors and compares intraoperative frozen-section margins to final histopathology. In addition, adjuvant therapy indications are provided. Study Design: Prospective cohort study. Setting: Academic university hospital. Subjects and Methods: Sixty-one patients with UP HNSCC were included. Patients received PET-CT, followed by oropharyngeal transoral laser microsurgery (TLM). Margins were assessed intraoperatively using frozen sections and afterward by final histopathology. Adjuvant treatment was based on final histopathology. Results: The sensitivity of localizing the primary tumor with PET-CT was 50.9% with a specificity of 82.5%. The primary tumor was found intraoperatively on frozen sections in 82% (n = 50) of patients. Five more tumors were identified on final histopathology, leading to a total of 90% (n = 55). Of the 50 intraoperatively found tumors, 98% (n = 49) had negative margins on frozen sections, and 90% (n = 45) were truly negative on final histopathology. Eighteen patients (29.5%) avoided adjuvant treatment. Conclusion: PET-CT localized the primary tumor in fewer than half the cases. This protocol identified 90% of primary tumors. Intraoperative frozen-section margin assessment has shown potential with a specificity of 92% compared to final histopathology. As a result, adjuvant therapy was avoided in almost one-third of our patients.